MANFAAT IKAN BAGI KESEHATAN (KAJIAN I’JAZ TIBBI QS.AN-NAHL AYAT 14 DALAM KITAB I’JAZ TIBBI FI AL-QUR’AN KARYA DR. SAYYID AL JUMAILI) - Miftakhul Karimah (AL-BAYAN INSTITUTE, 2025)
This study explores the scientific inimitability (i‘jaz tibbi) in the Qur’an concerning the health benefits of fish, focusing on the analysis of Surah An-Nahl verse 14 based on the interpretation of Dr. Sayyid Al-Jumaili. The phrase